Literatura e engajamento em Sartre: um estudo de Que é a literatura? - Guimarães, Frederico Moreira (2010)
This paper consists in analyse the conception of literature expressed in What is the Literature?, trying to elucidate what Sartre understands by engaged literature. This paper intends to show that the position of the author is linked in his biggest philosophical project, which means, the human s comprehension in the world from his condition as existent, whose unique basis is the freedom. Having its origin and ending in freedom, the literature runs towards the neighbor in which he belongs as human, his own freedom, and it is completed in a dialetic exercise of gratuities the reading. In this meaning, the mainly function of the engaged literature is to make it a mirror of the society itself in order to do men become conscious of themselves and of the reality and take their own decisions. The engaged literature, nevertheless, cannot be comprehended as an ideological pamphleteering, but as an action of the writer compromised to freedom and to his time